Advances in cerebellar disorders: pre-clinical models, therapeutic targets, and challenges - Manto, Mario; Cendelin, Jan; Strupp, Michael; Mitoma, Hiroshi (Expert opinion on therapeutic targets, 2023)
INTRODUCTION: Cerebellar ataxias (CAs) represent neurological disorders with multiple etiologies and a high phenotypic variability. Despite progress in the understanding of pathogenesis, few therapies are available so far. Closing the loop between preclinical studies and therapeutic trials is important, given the impact of CAs upon patients' health and the roles of the cerebellum in multiple domains. Because of a rapid advance in research on CAs, it is necessary to summarize the main findings and discuss future directions. AREAS COVERED: We focus our discussion on preclinical models, cerebellar reserve, the therapeutic management of CAs, and suitable surrogate markers. We searched Web of Science and PubMed using keywords relevant to cerebellar diseases, therapy, and preclinical models. EXPERT OPINION: There are many symptomatic and/or disease-modifying therapeutic approaches under investigation. For therapy development, preclinical studies, standardization of disease evaluation, safety assessment, and demonstration of clinical improvements are essential. Stage of the disease and the level of the cerebellar reserve determine the goals of the therapy. Deficits in multiple categories and heterogeneity of CAs may require disease-, stage-, and symptom-specific therapies. More research is needed to clarify how therapies targeting the cerebellum influence both basal ganglia and the cerebral cortex, poorly explored domains in CAs.
Keywords: Cerebellar Ataxia; Cerebellum; Cerebellar Diseases; cerebellum; DNA; mozeček; SCA; nemoci mozečku; cerebelární ataxie; reserve; metabolic; triplet; lidé; Humans; Purkinje; Ataxia